GENETIC ALGORITHM PERFORMANCE FOR ANALYSIS OF ELECTRONIC ORDER SCHEDULING - Paska Marto Hasugian; Harpingka Sibarani (Sean Institute, 2022)
Order scheduling is the process of organizing and arranging orders to be fulfilled by a certain time and date. This can be done manually or through the use of scheduling software. The goal of order scheduling is to ensure that orders are filled in a timely and efficient manner, while also being mindful of any constraints or limitations that may affect the fulfillment process. This can include factors such as inventory levels, production capacity and delivery times. This study specifically discusses the scheduling of electronic goods orders. Scheduling electronic goods orders is the process of organizing and managing orders for electronic goods to be fulfilled at a certain time and date. This scheduling can be done using software or systems that can assist in the process of planning and managing orders for electronic goods. Several factors to consider in scheduling electronic goods orders are inventory level, production capacity, delivery time, and demand from consumers. In optimizing the arrangement of order distribution schedules using a genetic algorithm, four parameters are needed, including the number of destinations, the number of sales, order crossover probability and mutation.